Cost Optimization for Renovation and Maintenance of Cultural Heritage Objects. (June 2019) - Macek, D; Heralová, R S; Hromada, E; Střelcová, I; Brožová, I; Vitásek, S; Pojar, J; Bouška, R
Abstract: The paper deals with the issue of maintenance and renovation of cultural heritage objects. This is a very specialised area of cost optimization, for which there can still be used procedures and methods applied to more normal contemporary objects, but where there are many peculiarities and differences that need to be taken into consideration. In the initial phase, it is necessary to gather all relevant data about such objects. From data there can be obtained information that can be used to build the structure and correlations of the recovery and maintenance model. In the Heritage Catalogue there can be found basic information about cultural heritage objects. It provides basic description of the objects, but technical data which could be used for creating the recovery and maintenance model are missing. Only if based on a sufficiently large and properly structured database, is it possible to deduce the correlations and dependencies needed to create a system for the types of planning and optimization involved in recovery and maintenance. In order to establish the recovery and maintenance costs, it is necessary to complement the database for individual construction elements costs and the length of recovery and maintenance cycles.